2021
DOI: 10.31234/osf.io/369ey
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Health Symptoms in Children and Adolescents during COVID-19 in Australia

Abstract: Objective: COVID-19 has led to disruptions to the lives of Australian families through social distancing, school closures, a temporary move to home-based online learning, and effective lockdown. Understanding the effects on youth mental health is crucial to inform policies to support communities as they face the pandemic and future crises. This paper sought to report on mental health symptoms in Australian children and adolescents during the initial stages of the pandemic (May to November 2020) and to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Whittle et al [15] similarly investigated associations between parent-factors and child (5-17 years old) mental health during COVID-19 and found signi cant associations between parental COVID-19-related stress, and parent depression, anxiety and stress symptoms, with increased child internalising and externalising problems. These ndings extend existing literature establishing a clear link between poorer parent mental health with poorer child mental health [16,17] by expanding to the pandemic context [14,18].…”
Section: Parent-related Vulnerability Factorssupporting
confidence: 85%
See 3 more Smart Citations
“…Whittle et al [15] similarly investigated associations between parent-factors and child (5-17 years old) mental health during COVID-19 and found signi cant associations between parental COVID-19-related stress, and parent depression, anxiety and stress symptoms, with increased child internalising and externalising problems. These ndings extend existing literature establishing a clear link between poorer parent mental health with poorer child mental health [16,17] by expanding to the pandemic context [14,18].…”
Section: Parent-related Vulnerability Factorssupporting
confidence: 85%
“…Accommodation may facilitate avoidance by reducing the need for children to implement effective coping strategies, inadvertently inhibiting their coping capacity. However, Sicouri et al [14] found that whilst worried children were more likely to seek parental reassurance in the context of the COVID-19 pandemic, symptoms were also partially attributed to the broader pandemic experience itself (rather than solely due to parental reassurance/accommodation behaviours). Given the cross-sectional nature of this study, whether accommodation occurs in response to expressed child mental health symptoms or vice versa during a pandemic remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…About 23% of parents who noted their child's mental health as excellent or very good prior to the COVID-19 pandemic, rated their child's emotional symptoms and conduct difficulties as high to very high. ∼16% of parents who reported their child's mental health as excellent or very good prior to the pandemic, reported clinical levels of anxiety and depressive symptoms in their child [5].…”
Section: Prevalence Of Depressive Anxiety and Other Psychiatric Sympt...mentioning
confidence: 99%